2014
DOI: 10.5812/archneurosci.17312
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Aquaporins in the Rat Choroid Plexus

Abstract: Background: Aquaporins (AQPs) are water channels that play a key role in water transport in many epithelia. Recent studies have shown that AQP1, located in the apical membrane of choroid plexus cells, has an important role in cerebrospinal fluid (CSF) production. However, the mechanism of water transport through the basolateral membrane of choroid plexus (CP) cells is yet to be determined. Objectives: In this study, the expression and localization of AQP1, AQP4 and AQP5 in the rat lateral ventricle CP were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 24 publications
(30 reference statements)
2
4
0
Order By: Relevance
“…Using Western blot we showed the presence of 33 and 23 kDa bands, which seems to be immunoreactive AQP1 protein, since their signals were completely or mostly blocked through using pre-adsorbed antibodies. Our results are similar to that obtained by Nesic et al (2008) demonstrating the presence of fuzzy band of 37 kDa in cytosolic fraction and 24 kDa band in the membrane fraction of rat spi- Nazari et al (2015) observed 32 and 27 kDa immunoreactive bands in the rat CP. According to Nielsen et al (1993) these bands may correspond with glycosylated and unglycosylated forms of AQP1, respectively.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Using Western blot we showed the presence of 33 and 23 kDa bands, which seems to be immunoreactive AQP1 protein, since their signals were completely or mostly blocked through using pre-adsorbed antibodies. Our results are similar to that obtained by Nesic et al (2008) demonstrating the presence of fuzzy band of 37 kDa in cytosolic fraction and 24 kDa band in the membrane fraction of rat spi- Nazari et al (2015) observed 32 and 27 kDa immunoreactive bands in the rat CP. According to Nielsen et al (1993) these bands may correspond with glycosylated and unglycosylated forms of AQP1, respectively.…”
Section: Discussionsupporting
confidence: 81%
“…According to Nielsen et al (1993) these bands may correspond with glycosylated and unglycosylated forms of AQP1, respectively. The localization of AQP4 in the ovine CP, which can be characterized as diffuse in the cytoplasm of epithelial cells, is in line with the findings of Speake et al (2003) and Nazari et al (2015). It has been demonstrated that rat AQP4 has six cDNA isoforms which are differentially expressed in the kidney and brain (Moe et al 2008).…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations